Single‐Step Microwave‐Mediated Synthesis of Oxazoles and Thiazoles from 3‐Oxetanone: A Synthetic and Computational Study. Issue 29 (13th June 2013) - Orr, David; Tolfrey, Alexandra; Percy, Jonathan M.; Frieman, Joanna; Harrison, Zoë A.; Campbell‐Crawford, Matthew; Patel, Vipulkumar K.
Abstract The direct microwave‐mediated condensation between 3‐oxetanone and primary amides and thioamides has delivered moderate to good yields of (hydroxymethyl)oxazoles and (hydroxymethyl)thiazoles. The reactions use a sustainable solvent and only require short reaction times. These are highly competitive methods for the construction of two classes of valuable heteroarenes, which bear a useful locus for further elaboration. Electronic structure calculations have shown that the order of events involves chalcogen atom attack at sp3 carbon and alkyl–oxygen cleavage. The critical role of acid catalysis was shown clearly, and the importance of acid strength was demonstrated. The calculated barriers were also fully consistent with the observed order of thioamide and amide reactivity. Spontaneous ring opening involves a modest degree of CO cleavage, moderating the extent of strain relief. On the acid‐catalysed pathway, CO cleavage is less extensive still, but proton transfer to the nucleofuge is well advanced with the carboxylic acid catalysts, and essentially complete with methanesulfonic acid.